2019
DOI: 10.1002/lary.27908
|View full text |Cite
|
Sign up to set email alerts
|

A 3D‐printed polycaprolactone/β‐tricalcium phosphate mandibular prosthesis: A pilot animal study

Abstract: Objective In this study, we assessed the effectiveness of a tonsil‐derived mesenchymal stem cell (TMSC)‐transplanted polycaprolactone/beta‐tricalcium phosphate prosthesis (specifically designed for easier fixing and grafting with a single scaffold) on rabbit mandible osteogenesis. Methods The mandibles of 18 rabbits were exposed, and 10 × 8‐mm bone defects were made. Two rabbits did not receive implants; four were reconstructed with the scaffold control (SC) (SC group); four were reconstructed with scaffolds s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…Similar attempts to fabricate PCL/T50 scaffolds for bone regeneration have been reported in previous studies. Owing to the difficulty of handling beta‐TCP in the rapid prototyping type of 3D printing, most studies applied PCL with less than 20% beta‐TCP 25,33‐36 . However, low concentrations of beta‐TCP resulted in a lack of significant differences between PCL and PCL/beta‐TCP in bone regeneration 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar attempts to fabricate PCL/T50 scaffolds for bone regeneration have been reported in previous studies. Owing to the difficulty of handling beta‐TCP in the rapid prototyping type of 3D printing, most studies applied PCL with less than 20% beta‐TCP 25,33‐36 . However, low concentrations of beta‐TCP resulted in a lack of significant differences between PCL and PCL/beta‐TCP in bone regeneration 37 .…”
Section: Discussionmentioning
confidence: 99%
“…80 assessed the effectiveness of a tonsil-derived mesenchymal stem cell on a transplanted PCL/beta-tricalcium phosphate scaffold on rabbit mandible in a 10 × 8-mm bone defect at 12 weeks and observed extended dense new bone masses. 81 Ho (2018) studied the effects of Biodentine/PCL scaffold with odontogenesis properties on human dental pulp cells. The Biodentine/PCL scaffolds were fabricated with uniform macropores 550 μm and interconnections using an extrusion printer.…”
Section: Cellular Bioactivity On Pcl Scaffoldsmentioning
confidence: 99%
“…Among the 89 selected articles, 9 did not perform biological tests to assess cell and bone growth, 17,23,26,41 59,64,68,88,102 evaluating the mechanical and morphological properties, 26,41,59,64,68,88,102 porosity and pore interconnectivity, 88 dissolution rates, 26,68 thermal stability, 26,41 surface wettability, 26,102 bacterial adhesion, 17 and antibacterial activity 41 . In order to assess cell and bone growth, 37 articles performed in vitro studies, 16,19–22,24,30,31,35,37–39,42,44–48,50, 54,56,60,62,63,67,70,71,78,79,87,89,90,101, 103,104,106,109 22 articles included in vivo assays, 7,9,10,14,25,28,32,36,40,43,57,58,61,65,66, 69,73–76,91,100 and 21 articles performed sequentially in vitro and in vivo studies 8,11–13,15,18,27,29,33,34,49,51–53,55,72,77,92,105,107,108 …”
Section: Resultsmentioning
confidence: 99%
“…79 In vivo studies included in this review indicated that scaffolds promote cell viability, migration, proliferation, and differentiation, inducing bone mineralization despite the used AM technique. 15,40,58,65,69 The animal studies show a favorable interaction between the scaffolds and the surrounding tissue. 8,[10][11][12][13] Furthermore, elements, such as TGFβ, BMP-2, and MSCs promote osteogenesis by inducing cell transformation towards the bone cell lineage.…”
Section: Discussionmentioning
confidence: 99%